Dextran‐Coated Ultrasmall Gd2O3 Nanoparticles as Potential T1 MRI Contrast Agent. Issue 19 (17th November 2016) - Xu, Wenlong; Miao, Xu; Oh, In‐Taek; Chae, Kwon Seok; Cha, Hyunsil; Chang, Yongmin; Lee, Gang Ho
Abstract: Ultrasmall gadolinium oxide (Gd2 O3 ) nanoparticles coated with dextran ( M ‾ r =1500 amu) were prepared through one‐pot synthesis and their potential to act as a T1 MRI contrast agent was investigated. The dextran‐coated ultrasmall Gd2 O3 nanoparticles were highly water‐dispersible, with an average particle diameter of 1.5 nm and an average hydrodynamic diameter of 12.4 nm, and non‐toxic, as determined in a cellular cytotoxicity test. The longitudinal (r1 ) and transverse (r2 ) water proton relaxivities were estimated to be 12.2 and 29.3 s −1 mM −1 (r2 /r1 =2.4), respectively, larger than those of commercial Gd‐chelates. This r1 value is also greater than those for previously reported dextran‐coated large Gd2 O3 nanoparticles with particle diameter bigger than 20 nm. Positive contrast magnetic resonance (MR) images were obtained after intravenous injection of a sample solution into a mouse tail, demonstrating the potential of dextran‐coated ultrasmall Gd2 O3 nanoparticles as a T1 MRI contrast agent. Abstract : The dextran‐coated ultrasmall Gd2 O3 nanoparticles (davg =1.5 nm) exhibited the r1 value of 12.2 s −1 mM −1 (r2 /r1 =2.4), superior to commercial Gd‐chelates and dextran‐coated large Gd2 O3 nanoparticles, and in vivo T1 MR images with positive contrasts were obtained after intravenous injection, demonstrating their potential as a T1 MRI contrast agent.